INSTAGLISH: WHEN INSTAGRAM IS BEYOND ONLINE PHOTO-SHARING PLATFORM TO INDUCE YOUR ENGLISH - Pusfika Rayuningtya; Ika Fitriani (ETERNAL (English, Teaching, Learning and Research Journal), 2021)
Motivated by the growth of social media throughout the globe, including in Indonesia, educational practitioners need to be creative and make use of this opportunity to boost up the learning goals, for example making use of Facebook, Twitter, Instagram, Line, and many others (social media) in educational settings. Among those social media, Instagram has increased its popularity, particularly in Indonesia, with its 22 million users. It is an online platform in which users can share their stories via uploaded photos. Recently, it is not merely used as photo story sharing but also online shopping, news updating, and video conferencing. As Instagram offers promising features, this study explored how this platform was applied to improve the students English written competence, focusing on reading and writing. This study is action research that investigates the use of Instagram as a social-and-educational medium that offers beyond new language learning experiences in the project called InstaGlish, Instagram English. The data were collected from the classroom observation during the project, students' Instagram photo posts, captions and comments, and students' reading and writing scores after project implementation.  A questionnaire and direct interview to the students were also carried out to give a more thorough and deeper understanding of the students' responses toward how effective InstaGlish helps them learn and induce their English. In addition, the findings of this current study were expected to give fruitful insight on how to use social media not merely as the fun-without-meaning activity yet fun-and-meaningful new learning experiences.